Laying Hens Analysis In Taba Lagan Bengkulu Tengah Regency - Rita Feni; Nurul Pratiwi; Jafrizal Jafrizal; Edi Efrita (UNIVED Press, Dehasen University Bengkulu, 2022)
Central Bengkulu is one of regency in Bengkulu province that has potency in laying hens farm. This study aims to know the profit, efficiency (B/C Ratio) and Break Event Point (BEP) of laying hens farm in Desa Taba Lagan Central Bengkulu regency of Bengkulu Province. This study done in Desa Taba Lagan Central Bengkulu regency between June and August of 2022. The study concluded that laying hens farm profit as Rp 196.599.000 per production season (18 months) with 12.000 hens. R/C ratio value as 1,039, B/C ratio value 0,039 and BEP production at 117.725 crate, and BEP sales at Rp 5.062.175.000